Discovery of Open Cubane Core Structures for Biomimetic LnCo3(OR)4 Water Oxidation Catalysts. Issue 22 (24th October 2017) - Schilling, Mauro; Hodel, Florian H.; Luber, Sandra
Abstract: Bio‐mimetic catalysts such asLnCo3 (OR)4 (Ln=Er, Tm; OR=alkoxide) cubanes have recently been in the focus of research for artificial water oxidation processes. Previously, the remarkable adaptability with respect to ligand shell, nuclear structure as well as protonation and oxidation states of those catalysts has been shown to be beneficial for the water oxidation process. We further explored the structural flexibility of those catalysts and present here a series of novel structures in which one metal center is pulled out of the cubane cage. This leads to an open cubane core, which is to some extent reminiscent of observed open/closed cubane‐core forms of the oxygen‐evolving complex in nature's photosystem II. We investigate how those open cubane core models alter the thermodynamics of the water oxidation cycle and how different solvation approaches influence their stability. Abstract : Out of the cage : We report new open cubane core structures for LnCo3 (OR)4 (Ln=Er, Tm, OR=alkoxide) water oxidation catalysts and investigate the influence of implicit and explicit solvation on those structures.